2023
DOI: 10.21203/rs.3.rs-2586639/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reference intervals and sources of variation of pressure pain threshold for quantitative sensory testing in a Japanese population

Abstract: Quantitative sensory testing (QST) is useful when analysing musculoskeletal pain disorders. A handheld algometer is most commonly used for pressure pain threshold (PPT) tests. However, reference intervals for PPTs are not elucidated. We assessed reference intervals of PPTs for QST in 158 healthy adult Japanese (73 females, 85 males) with no history of musculoskeletal or neurological problems. A handheld algometer was used to record PPT at five different assessment sites on the body: lumbar paravertebral muscle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…While PPT is not directly linked to musculoskeletal pathology, it provides valuable insight into a patient's perception of local pain responses. Previous research has confirmed that patients with chronic LBP exhibit lower PPT 11 and that PPT can identify patients with and without LBP 16 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…While PPT is not directly linked to musculoskeletal pathology, it provides valuable insight into a patient's perception of local pain responses. Previous research has confirmed that patients with chronic LBP exhibit lower PPT 11 and that PPT can identify patients with and without LBP 16 .…”
Section: Discussionmentioning
confidence: 87%
“…When assessing PPT in the lumbar region, research indicates no discernable sex-based variances in healthy individuals but observes differences in males and females with LBP. When measuring PPT in the lumbar spine of healthy Japanese subjects (mean PPT ≈530 kPa), there were no sex-based differences in PPT values from the lumbar spine 16 . PPT values from the lumbar spine for healthy subjects from Brazil also reported no differences in males and females (mean PPT ≈350 kPa; mean age: 47-51 years; p = 0.3, n = 12-18 per group) 17 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation